Exploring the Complex Interaction Between Governance and Knowledge in Education - Fazekas, Mihály (OECD Publishing, 2012)
Governments in all OECD countries are facing the challenge of governing increasingly complex education systems. There is a growing need for governance structures that can handle this complexity and which can provide actors with the knowledge they need to make decisions. This working paper asks the question: How do governance and knowledge mutually constitute and impact on each other in complex education systems? It provides an answer through a state of the art literature review and original theoretical argumentation. It breaks new ground by combining different schools of academic and policy thinking which traditionally look at various aspects of the relationship between governance and knowledge separately. Research in public management, political science and public policy, sociology, institutional economics, and organisational management (particularly the knowledge transfer literature) is augmented with work from education and other social sciences, including healthcare, law, and social justice. This working paper argues that just as knowledge is crucial for governance, governance is indispensible for knowledge creation and dissemination. It proposes an analytical framework that combines models of governance with modes of learning and types of knowledge, and provides preliminary empirical examples to support this framework. In the context of diverse social, economic and political environments of OECD countries, the interaction between these two focal points - models of governance and types of knowledge - has become increasingly relevant to researchers, policy makers, and education stakeholders more generally
Keywords: Education